Understanding participation in community education and development - Megat Tajudin, Putri Noorafedah; Idris, Khairuddin; Abd Rahim, Nuraira; Arshad, Mohd. Mursyid (Secholian Publication, 2019)
The term "participation” is of relatively gaining popularity in many fields, even though the phenomenon it refers to has been highlighted decades ago. The concept provided a useful awareness on community education and development programs and empowerment. Community participation has become a focus of various agencies and organizations. Many are beginning to recognize community participation as a key to improve the social wellbeing and quality of life, especially to the under privilege groups. This brief and general article presents introduction to community education and development, definitions of participation and the most referred typologies of participation.